Applying management by objective as an organizational development intervention for improving employee productivity, job satisfaction, performance, and customer satisfaction: A case study of a company in Thailand - Fan, Ting Ting (Nurture, 2023)
Purpose: The study applied the Management by Objectives (MBO) method for organizational development intervention (ODI) for enhancing employee productivity, job satisfaction, performance, and customer satisfaction. Design/Methodology/Approach: A total of 33 people were involved under the tools of observations, interviews, and primary data analysis from employees, suppliers, and customers. This study employed qualitative methodologies, specifically open-ended interview questions, to guide the approaches leveraged during pre-ODI, diagnosis, and post-intervention. Findings: Based on the findings, MBO is critical in improving internal circumstances at focal organization, which helped to increase employee productivity, job satisfaction, performance, and customer satisfaction and build more alignment within the organization. Conclusion: The organization failed to engage its employees successfully as a result of a lacking MBO process coupled with ineffective employee involvement. This led to poorer performance and lower productivity among employees, as well as decreased job satisfaction. Research Limitations/Implications: The current study was conducted by the CEO, and the limitations arising are that employees may not be able to answer the questions with honesty about their prospects. Practical Implications: The research has offered a vital understanding of MBO as an intervention tool and highlighted how companies in similar sectors could embrace the practice of MBO to improve employee productivity, job satisfaction, performance, and customer satisfaction, which will benefit the industry. Contribution to Literature: The study lied in the ability of MBO in the home shopping industry, as it affected the performance of employees, which was critical to improving organizational outcomes. All of the above contributed to the uniqueness of this study.